The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0021998316665241
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose fiber-reinforced high-density polyethylene composites—Mechanical and thermal properties

Abstract: In this investigation, the thermal and mechanical properties of cellulose fibers from sugarcane bagasse reinforced with high density polyethylene composites were evaluated. Cellulose fibers were modified with hydrous Zr oxide to clean the fiber surface and improve the fibers-matrix adhesion. Composites were manufactured using a thermokinetic mixer process and the fiber content was responsible for 5, 10, 20, 30, and 40wt% in the composition. The chemical modification of the cellulose fibers with zirconium oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…Theses longitudinal fibres of the composites, oriented transversely to the direction of the impact pendulum, may realize friction in the matrix and dampen a greater amount of energy. According to Mulinari et al [35], brittle behavior of fibres can limit the plasticity behavior of the composites because of mechanical friction process, resulting in the fibre pull-out from the matrix. Zhao et al…”
Section: Fracture Analysis Of the Compositesmentioning
confidence: 99%
“…Theses longitudinal fibres of the composites, oriented transversely to the direction of the impact pendulum, may realize friction in the matrix and dampen a greater amount of energy. According to Mulinari et al [35], brittle behavior of fibres can limit the plasticity behavior of the composites because of mechanical friction process, resulting in the fibre pull-out from the matrix. Zhao et al…”
Section: Fracture Analysis Of the Compositesmentioning
confidence: 99%
“…7 This materials class has been used in different areas, such as in architectural material and automotive industry. 8…”
Section: Introductionmentioning
confidence: 99%
“…The absorption bands at approximately 1638 cm -1 and 3430 cm -1 were assigned to the vibrations of water molecules (Ramandi et al 2017). The absorption peaks at 1732 cm -1 and 2885 cm -1 , i.e., the characteristics of unconjugated CO groups and symmetrical CH groups in hemicelluloses, showed a decreased intensity, which indicated that the hemicelluloses were partly degraded during the in situ process (Mulinari et al 2016). To further clarify the compositions of the iron oxide compounds and copper film, the high-resolution XPS spectra of Fe 2p, O 1s, and Cu 2p3/2 were measured (Figs.…”
Section: Characterizations Via Sem Eds Xrd Ftir and Xpsmentioning
confidence: 99%